Identification of structural parameters and hydrodynamic effects for forced and free vibration - Kruchoski, Brian L. (Brian Louis) (2013)
Statistically-based estimation techniques are presented in this study. These techniques incorporate structural test data to improve finite element models used for dynamic analysis. Methods are developed to identify optimum values of the parameters of finite element models describing structures. The parameters which may be identified are : element area, mass density, and moment of inertia; lumped mass and stiffness; and the Rayleigh damping coefficients. A technique is described for incorporating hydrodynamic effects on small bodies by identifying equivalent structure mass, stiffness, and damping properties. Procedures are presented for both the free vibration problem and for forced response in the time domain. The equations for parameter identification are formulated in terms of measured response, calculated response, the prior estimate of the parameters, and a weighting matrix. The form of the weighting matrix is presented for three identification schemes : Least Squares, Weighted Least Squares, and Bayesian. The weighting matrix is shown to be a function of a sensitivity matrix relating structural response to the parameters of the finite element model. Sensitivities for the forced vibration problem are derived from the Wilson Theta equations, and are presented for the free vibration problem. The algorithm used for parameter identification is presented, and its implementation in a computer program is described. Numerical examples are included to demonstrate the solution technique and the validity and capability of the identification method. All three estimation schemes are found to provide efficient and reliable parameter identification for many modeling situations. === Graduation date: 1993